“Gimnasia, Música y Patria”: exhibiciones gimnásticas en el franquismo. El caso de los Festivales salesianos y el XIV Campeonato Nacional de Gimnasia Educativa (“Gymnastics, Music and Homeland”: gymnastic exhibitions during Franco´s regime. The case of sa - Ayala Herrera, Isabel María; Zagalaz Sánchez, María Luisa (Retos, 2016)
El hallazgo en la Biblioteca Nacional y el Archivo General de la Administración de dos fuentes documentales de gran valor (los Festivales Gimnásticos de la Galería Salesiana [192?] y las tablas con música del XIV Campeonato Nacional de Gimnasia Educativa [1961-1963]), prácticamente ignoradas hasta el momento, ha impulsado este trabajo cuyo principal objetivo es la reconstrucción historicista de prácticas de gimnasia educativa en el franquismo a través de la transcripción, ensamblaje de partes, análisis y correlación de parámetros músico-corporales, edición y estudio crítico de los ejercicios corporales, sonidos y letras contenidas en ellas, alumbradoras de su contexto. El estudio concluye que Gimnasia, Música y, sobre todo, su correcto acoplamiento, fueron piedra de toque en el ideario del Movimiento por el enorme beneficio que reportaban a la educación moral e intelectual de los jóvenes, empleándose además como eficaz medio de propaganda en grandes fastos y exhibiciones gimnásticas, auténticos escaparates patrióticos en los que, de forma masiva y entusiasta, se moldeaba y elevaba el espíritu nacional de participantes y espectadores. Abstract. The finding in the National Library and Administration’s General Archive of two valuable documentary sources (the Gymnastics Festivals of the Salesian Gallery [192?] and the obligatory set of exercises with music of the 14th National Championship of Educational Gymnastics [1961-1963]), virtually ignored until now, has driven this work. The main aim of this article is the historicist reconstruction of educational gymnastics practices during Franco´s regime through transcription, parts assembly, analysis and correlation between music and movement, edition and critical study of body exercises, sounds and letters contained therein, which shed light into their context. The study concludes that Gymnastics, Music and, especially, its right coupling were the touchstone of the esthetic and educational ideology of the Movement, as they were thought to bring an enormous benefit to the moral and intellectual education of young people. At the same time, the above mentioned disciplines were used as effective propaganda, fundamentally by means of the organization of great pomp, performances and gymnastics exhibitions, which proved an authentic patriotic window to the world, in which, in a massive and enthusiast way, the national spirit of participants and spectators was moulded and lifted.